Infectious endocarditis in HIV-infected intensive care unit patients - T. V. Kharlamova; S. L. Voznesenskiy; T. N. Ermak; G. M. Kozhevnikova; P. V. Klimkova (Журнал инфектологии)
Infective endocarditis (IE) is one of the most common cardiac complications in HIV patients who are intravenous drug addicts. The presence of IE and secondary diseases in immunocompromised individuals usually requires specific diagnostic and therapeutic approach.Aim: Optimizing the diagnosis of IE in patients with advanced HIV/AIDS.Materials and methods We reviewed 429 case records of HIV/AIDS ICU patients using the modified duke criteria for diagnosis of infective endocarditis. Statistical significance (p <0.05) of data was assessed using the χ2 test.Results. 25 patients were diagnosed with IE. The male gender dominated – 68%. Mean age was 38. 60% had stage 4B HIV infection. 68% were ART naive. The medium viral load was 294560 copies / ml, while the medium CD4 count was 218 cells / μl. Fever of >38°C was a key symptom found in all patients. Blood cultures were positive in 60% cases. 80% had a high C reactive protein (CRP), and 44% had CRP levels above 100 mg/l. Procalcitonin (PCT) levels were increased in 52%. Echocardiogram revealed IE in 92%. Pneumonia was diagnosed in 92%. Fatal outcome occurred in 76%. Anemia was a predictor of severe outcome (p<0.002), while patients with leukocytosis had good prognosis (p<0.05).Conclusion. Infective endocarditis is a common complication among HIV IDUs. The most common diagnostic criteria are fever >38°C, pneumonia, anemia, leukocytosis, thrombocytopenia and echocardiographic findings. The levels of the hemoglobin and WBCs could evaluate prognosis of the disease outcome.